Implementasi Pembelajaran Pendidikan Agama Islam Dalam Keluarga Santri - Lathifatul Izzah (Universitas Alma Ata, 2020)
This paper aims to describe and analyze the process and implications of the implementation of Islamic religious education learning in santri families in Wonolelo village, Pleret district, Bantul district. Qualitative methods with the type of case study research are used to reveal these expectations. Data collection was carried out by observation, interviews, and documentation. The collected data were analyzed by analytical induction.The process of implementing Islamic religious education learning in the santri family can be carried out through planning, implementation and evaluation. The third process can be successful, influenced by various factors. Among them are materials, methods, environment, technology, and cooperation or cohesiveness between family members, especially both parents. Finally, family education can have an impact or have implications for the character of family members, especially children as themselves, relating to Allah, the Lord of the Universe, God's fellow creatures. Keywords: Implimentation, learning, Islamic religious education, santri families